Parasitismo de cría del Renegrido, Molothrus bonariensis, sobre el Chingolo, Zonotrichia capensis : nuevas observaciones y conclusiones - Fraga, Rosendo Manuel (1983)
Data on the brood parasitism of the Shiny Cowbird, Molothrus bonariensis on the Rufous-collared Sparrow, Zonotrlchia capensis, was collected during 10 breeding seasons (l970-1979: 70 nests), in a study site at Buenos Aires Province, Argentina. Though the cowbird parasitised 14 species of local passerines (40 %"of the total) most parasitic fledglings (46%), were reared by the sparrows. During the breeding season sparrows considerably outnumbered the cowbirds. Home ranges of banded female cowbirds ranged in size from 21 to 48 ha, and other females were not excluded; the females were rather gregarius.After 1975 the incidence of parasitism in nests of sparrows declined significantly; the overall incidence was 61,90%. Two morphs of cowbirds eggs were found in similar proportions in sparrow nests; measurements, size and shape of the egg morphs are included. The distribution of all cowbirds eggs in the nests of this accepter host departed significantly from Poisson and Preston (1948) distributions, but those of separate egg morphs agreed closely with expected distribution. Cowbird females laid 1 or 2 eggs per sparrow nest; with 1 exception, sets of 3 or more cowbird eggs represent parasitism by 2 or more females. The nesting success of host and parasite was low, being only 5,56% for cowbird eggs. Cowbirds destroyed relatively few (6,58%) cowbird eggs. In order to have 1 fledgling cowbird reared by sparrows each breeding season female cowbirds should lay 18 eggs in the nests of this host. The results are compared with those of other studies.